High-strength heat-resistant aluminum-manganese-iron alloy and preparation method thereof

By adding Mn, Fe and rare earth elements to the aluminum alloy, strengthening phase particles with core-shell structure are formed, which solves the problem of insufficient performance of aluminum alloy in high temperature environments, and achieves both high strength and heat resistance. It is suitable for High temperature components in the aerospace field.

CN119464849APending Publication Date: 2025-02-18CENT SOUTH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411661953.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing aluminum alloys are insufficient in high temperature environments, especially in high-temperature components applications in the aerospace field, and it is difficult to meet the requirements of heat resistance and mechanical properties.

Method used

Al6(Mn,Fe) particles with core-shell structure are formed by adding Mn and Fe elements to the aluminum alloy, and rare earth elements and Zr and Al are introduced to form reinforced phase particles Al3(Re,Zr) to improve the heat resistance of the alloy. and strength.

Benefits of technology

It realizes high strength and heat resistance of aluminum-manganese alloy in high temperature environments, and has excellent mechanical properties at room temperature and high temperatures, and is suitable for high-temperature components in the aerospace field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464849A_ABST
    Figure CN119464849A_ABST
Patent Text Reader

Abstract

The invention relates to the field of additive manufacturing, and provides a high-strength heat-resistant aluminum-manganese-iron alloy and a preparation method thereof. The alloy is prepared from the following raw materials in percentage by mass: 4.5 to 9.0 weight percent of Mn, 0.5 to 3.5 weight percent of Fe, 0.2 to 1.5 weight percent of Zr, 0.4 to 2 weight percent of Re and the balance of Al and inevitable impurities, re is Sc and / or Er. The aluminum-manganese-iron alloy is prepared through a selective laser melting forming technology, the density of an optimized product can reach 99.5% or above, the room-temperature tensile strength can reach 584 MPa after aging strengthening, the ductility can reach 15%, and at the high temperature of 350 DEG C, the tensile strength can reach 256 MPa, and the ductility can reach 4.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of additive manufacturing and relates to a high-strength heat-resistant aluminum-manganese-iron alloy and a preparation method thereof. Background Art

[0002] Aluminum alloys have been widely used in the aerospace field due to their excellent specific strength, good corrosion resistance and outstanding durability. However, meeting the stringent requirements for heat resistance in the aerospace field remains a challenge, especially when it comes to high-temperature parts, such as critical components such as rocket nozzles, heat shields and engine pistons. Currently, commercial heat-resistant aluminum alloys mainly include aluminum-silicon alloys and aluminum-copper alloys, which are enhanced by coherent metastable precipitates (such as Al2Cu and AlMgCuSi) introduced by solid-state reactions. However, the rapid coarsening of the reinforcing phase limits the long-term use of these alloys in environments above 250°C. With the increase of temperature, the microstructure of aluminum alloys is prone to change, resulting in a significant decrease in mechanical properties.

[0003] In addition, traditional manufacturing processes often have difficulty in producing complex shapes and high-performance components, which further limits the application of heat-resistant aluminum alloys. Therefore, it is urgent to develop a new type of heat-resistant aluminum alloy to achieve superior high-temperature performance. Additive manufacturing, as an emerging manufacturing technology, provides distinct advantages over traditional methods. This technology can not only effectively reduce material waste, but also achieve more complex geometries, allowing designers to create components with more efficient thermal management characteristics.

[0004] Chinese patent CN114411023A discloses a high-toughness aluminum alloy powder material for laser additive manufacturing, which adds Mg and Ti elements to the Al matrix, and adds Zr elements to form a dispersed phase with Ti, which plays a role of dispersion strengthening during the heat treatment process, and adds Mn elements to improve its weldability. The 3D printing method is used to realize the interaction of each element in the multi-element alloy, which also greatly improves the restriction of the solid solubility of the components on the improvement of material performance, and finally enables the aluminum alloy powder material to achieve excellent strength and toughness. However, the precipitation strengthening effect introduced by the Ti element in this patent is mainly achieved through Al3Ti or other intermediate phases, and the strengthening effect and thermal stability of these phases are relatively weak, especially in high-temperature applications, the tensile strength is not improved enough.

[0005] In order to expand the application range of aluminum alloys in high temperature environments, the development of aluminum alloy powders suitable for additive manufacturing that can maintain high strength and plasticity under high temperature conditions will be the focus of current research. By adjusting the alloy composition and optimizing the additive manufacturing process parameters, it is expected that new aluminum alloys with excellent heat resistance will be prepared. These alloys will not only meet the performance requirements in high temperature environments, but will also provide more possibilities for innovative designs in the aerospace field, thereby promoting technological progress in the entire industry. Summary of the invention

[0006] In view of the insufficient performance of the prior art aluminum alloys in high temperature environments, the first object of the present invention is to provide a high-strength and heat-resistant aluminum-manganese-iron alloy. The alloy improves the heat resistance of the alloy by adding Mn and Fe elements to form Al6 (Mn, Fe) particles with a core-shell structure, and at the same time introduces rare earth elements and Zr to form strengthening phase particles Al3 (Re, Zr) with Al to further improve the strength and thermal stability of the alloy, so that the aluminum-manganese-iron alloy has both high strength and heat resistance.

[0007] The second object of the present invention is to provide a method for preparing a high-strength and heat-resistant aluminum-manganese-iron alloy. The high-strength and heat-resistant aluminum-manganese-iron alloy designed by the present invention can be further improved in terms of comprehensive performance after being formed by additive manufacturing and combined with heat treatment technology.

[0008] In order to achieve the above technical objectives, the present invention provides a high-strength heat-resistant aluminum-manganese-iron alloy, the raw materials of which include the following components by mass percentage: Mn 4.5-9.0wt%, Fe 0.5-3.5wt%, Zr0.2-1.5wt%, Re0.4-2wt%, and the rest are Al and unavoidable impurities; the Re is Sc and / or Er.

[0009] The key to the technical solution of the present invention lies in the design of components and the control of dosage. Specifically, Mn is first added as the main alloy component in the added alloy components. The addition of Mn can significantly reduce the sensitivity of hot cracks. This is because Mn-rich particles can slow down the stress concentration in the alloy and evenly distribute the stress, thereby reducing the tendency of hot cracks and improving the formability of the additively manufactured aluminum-manganese alloy. The Mn element has a low diffusion coefficient and low solid solubility in aluminum, and can form a stable second phase (Al6Mn phase) with a melting point, maintain the stability of the alloy's structure at high temperatures, reduce softening, and thus improve the heat resistance of the alloy. At the same time, by adding an appropriate amount of Fe element, the extremely low solid solubility of Fe element is combined with Mn element to increase the nucleation site of the grain, thereby forming Al6 (Mn, Fe) with a core-shell structure and further promoting the fine dispersion distribution of Al6 (Mn, Fe) particles, which significantly improves the tensile strength and heat resistance of the alloy. The control of Mn and Fe content is the key to component design. Excessive addition of Mn and Fe elements will lead to a decrease in the plasticity of the alloy. When the amount of Mn and Fe is too small, on the one hand, sufficient Al6Mn second phase cannot be formed, and on the other hand, Al6(Mn,Fe) with a core-shell structure cannot be further formed, so it is impossible to effectively alleviate the stress concentration in the alloy and reduce the tendency of thermal crack formation. In addition, the present invention adds a small amount of rare earth elements on this basis. When the rare earth elements are added, they will form Al3Re phases with aluminum, and dispersed precipitation phases can be formed at the grain boundaries and in the grains, providing a significant precipitation strengthening effect. These Al3Re particles have high thermal stability and high shear resistance, and can still maintain their strengthening effect at high temperatures. In particular, when the rare earth element is Sc and / or Er, the composite addition of Zr can further form a core-shell structured strengthening phase particle Al3 (Sc, Zr) or Al3 (Er, Zr), which has Re as the core and Zr as the shell. The slow diffusion rate of Zr as the shell is conducive to further improving the thermal stability of the strengthening phase particles. Compared with the precipitation strengthening effect introduced by the commonly used Ti element in the prior art, the strengthening effect and thermal stability of the strengthening phase particles of the present invention are improved. Therefore, the alloy obtained by the present invention has both high strength and heat resistance in a high temperature environment. It is further preferred that Re is a combination of Sc and Er.

[0010] As a preferred solution, the mass ratio of Re and Zr is 1:(0.5-0.8). The two are added together because Re can significantly refine the grains of aluminum alloys, and the addition of Zr to aluminum alloys can further enhance this grain refinement effect. Under the synergistic effect of the two, the grains of aluminum alloys are finer, which helps to improve its mechanical properties, especially tensile strength and corrosion resistance. And Re needs to be slightly excessive than Zr. When added in the above ratio, it is more conducive to constructing fine and dispersed nanoparticles with a core-shell structure, with Al3Re as the core and Al3Zr as the shell. The special structure enhances the stability of the nano-precipitated phase. Further improve the thermal stability of aluminum alloys, especially at high temperatures, when Sc and Zr are used in combination, the high temperature annealing resistance of the alloy can be enhanced.

[0011] As a preferred solution, the raw materials include the following components by mass percentage: Mn 4.5-5.0wt%, Fe 1.5-3.5wt%, Zr 0.2-0.75wt%, Re 1.5-2wt%, and the rest is Al and inevitable impurities. Within the further preferred raw material range, an alloy with the best comprehensive performance can be obtained.

[0012] When the aluminum alloy material requires optimal elongation at high temperature during application, the alloy composition may further preferably include the following components: Mn 4.5-5.0wt%, Fe 0.5-1wt%, Zr 0.2-0.75wt%, Sc 1.5-2wt%, and the rest is Al and inevitable impurities.

[0013] When the aluminum alloy material requires optimal room temperature and high temperature strength during application, the alloy composition may further preferably include the following components: Mn 4.5-5.0wt%, Fe 3-3.5wt%, Zr 0.2-0.75wt%, Re 1.5-2wt%, and the rest is Al and inevitable impurities.

[0014] As a preferred solution, the aluminum matrix in the alloy is a heterogeneous structure with alternating coarse and fine grains, and there are primary Al6 (Mn, Fe) and Al3 (Re, Zr) precipitation phase particles on the subgrain boundaries or in the grains in the alloy matrix, and after aging, secondary phases are precipitated in the matrix, which has secondary core-shell structure Al6 (Mn, Fe) and Al3 (Re, Zr) strengthening phase particles, wherein the size of the primary phase particles is larger than the secondary phase particles, the total volume fraction of Al6 (Mn, Fe) particles is between 12% and 22%, and as the volume fraction of Al6 (Mn, Fe) particles increases, the strengthening effect of the second phase particles is obvious. The grain distribution of the present invention can greatly improve the room temperature strength and high temperature strength of the alloy.

[0015] The present invention also provides a method for preparing a high-strength and heat-resistant aluminum-manganese-iron alloy. The method comprises the following steps: weighing each component according to the designed aluminum-manganese-iron alloy component ratio, smelting the aluminum-manganese master alloy, the aluminum-iron master alloy, the aluminum-rex master alloy, the aluminum-Re master alloy, and aluminum, and then pulverizing the pulverized aluminum-manganese-iron alloy powder by gas atomization to obtain the aluminum-manganese-iron alloy powder; and the aluminum-manganese-iron alloy powder is obtained by laser additive manufacturing and isothermal aging heat treatment.

[0016] The alloy components designed by the present invention can further improve the overall performance of the alloy when combined with the preparation method of the present invention. The principle is: Mn with a slow diffusion coefficient is selected as the main alloy additive component, and a nano-scale Mn-rich supersaturated solid solution can be obtained by controlling the process parameters of additive manufacturing. The temperature and time are further screened by aging treatment to obtain Al6Mn particles with a certain content, and finally achieve high strength and heat resistance of the alloy. Further, through the composite addition of MnFe and the composite addition of ZrRe, the same aging process induces the formation of Al6(Mn,Fe) particles and Al3(Re,Zr) particles with a certain content and a core-shell structure, further improving the strength and heat resistance of the alloy.

[0017] As a preferred solution, the melting temperature is 950-1100°C, and ultrasonic stirring is used after melting to promote uniform mixing of the melt. In the present invention, the melting temperature only needs to be higher than the melting point of the raw material.

[0018] As a preferred solution, the process parameters of the laser additive manufacturing are: laser spot diameter 100-130μm, scanning power maintained between 300-400W, scanning speed maintained between 1100-1700mm / s, laser scanning spacing 80-140μm, powder thickness 35-80μm, scanning strategy is chessboard scanning, strip scanning or honeycomb scanning; the protective gas is Ar, the oxygen content is less than 0.1%, the substrate heating temperature is 100-150℃, and the aluminum-manganese-iron alloy powder particle size used is 20-48μm. The change of process parameters in additive manufacturing also has a certain influence on the performance of the alloy. For example, if the scanning power in the scanning parameters is too low, the scanning speed is too high, and the layer thickness is too large, the forming energy density will be too low, and it is easy to introduce defects such as unfusion, thereby causing the strength of the alloy to decrease. In addition, if the scanning power is too high, the scanning speed is too low, and the layer thickness is too small, the forming energy density will be too high, and defects such as pores will be easily introduced, thereby causing the plasticity of the alloy to decrease.

[0019] As a preferred solution, the temperature of the isothermal aging treatment is 250-375°C, and the holding time is 1-48h. The present invention adopts isothermal aging treatment to reduce the internal residual stress of the material, and also improves the yield strength and plasticity of the material. If the temperature of the isothermal aging treatment is too high and the time is too long, the precipitation phase will grow abnormally and reduce the strength of the alloy. In addition, if the temperature of the isothermal aging treatment is too low and the time is too short, the precipitation phases Al6 (Mn, Fe) and Al3 (Re, Zr) will fail to effectively precipitate and strengthen the alloy.

[0020] As a preferred solution, the temperature of the isothermal aging treatment is 300-350°C, and the holding time is 8-12 hours. In a further preferred range of the aging treatment temperature and holding time, a product with the best alloy strength and heat resistance can be obtained. Furthermore, the isothermal aging treatment temperature is 300-325°C.

[0021] The present invention provides a method for preparing a high-strength heat-resistant aluminum-manganese-iron alloy, which specifically comprises the following steps:

[0022] 1) Preparation of powder

[0023] According to the designed aluminum-manganese-iron alloy component ratio, each component is weighed, and the aluminum-manganese master alloy, aluminum-iron master alloy, aluminum-rex master alloy, aluminum-Re master alloy, and aluminum are heated in a high-temperature furnace to a molten state, the temperature being higher than the melting point of the material (950-1100°C), and the molten body is stirred by ultrasonic to make it uniformly mixed;

[0024] The gas atomization technology is used for the molten high-strength and heat-resistant aluminum alloy powder. High-pressure gas (such as nitrogen or argon) is usually used for gas atomization. The molten metal is sprayed through a nozzle. The high-pressure gas quickly disperses the molten metal stream into small droplets. During the atomization process, the metal droplets are quickly cooled in the gas flow and solidified into powder.

[0025] 2) Laser Additive Manufacturing

[0026] Aluminum-manganese-iron-aluminum alloy is formed by selective laser melting technology. The process parameters are: laser spot diameter 100-130μm, scanning power maintained between 300-400W, scanning speed maintained between 1100-1700mm / s, laser scanning spacing 80-140μm, powder thickness 35-80μm, scanning strategies of chessboard scanning, strip scanning and honeycomb scanning; protective gas is Ar, oxygen content is less than 0.1%, and substrate heating temperature is 100-150℃.

[0027] 3) Heat treatment

[0028] Isothermal aging experiments were carried out on the printed aluminum-manganese-iron alloy products to optimize the alloy strength. The printed samples were aged at 250-375°C for about 1 to 48 hours.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The heat-resistant aluminum alloy powder prepared by the present invention can obtain a large amount of low-cost spherical powder with good fluidity through the combination of ultrasonic stirring and inert gas atomization technology, which can promote product application.

[0031] (2) The addition of an appropriate amount of Fe in the present invention can improve the tensile strength of the material, and quasi-crystalline phase particles with a core-shell structure exist in the rapidly solidified powder. The presence of Al6 (Mn, Fe) and Al3 (Re, Zr) precipitation phase particles on the subgrain boundaries or in the crystals in the matrix greatly improves the room temperature strength and high temperature strength. The improvement in mechanical properties is due to its fine subgrain structure and other dispersed particles.

[0032] (3) Rare earth elements Re (Sc scandium, Er erbium) and Zr have low solubility and low diffusion rate in the aluminum matrix, achieving the effect of modification. They react with the matrix Al to form Al3 (Re, Zr), which is dispersed in the matrix, reducing the coarsening of the grains and playing a role of dispersion strengthening. They pin dislocations in the alloy matrix, hindering dislocation movement and achieving the purpose of improving strength.

[0033] (4) The present invention selects Mn with a slow diffusion coefficient as the main alloy component, obtains a Mn-rich supersaturated solid solution by additive manufacturing, and further obtains Al6Mn particles with a certain content through aging treatment, ultimately achieving high strength and heat resistance of the alloy; further, through the composite addition of MnFe, the same aging process induces the formation of Al6(Mn,Fe) particles with a certain content and a core-shell structure, further improving the strength and heat resistance of the alloy.

[0034] (5) The present invention performs an isothermal aging heat treatment process on the aluminum alloy after additive manufacturing, which can reduce the residual stress inside the material on the one hand, and improve the yield strength and plasticity of the material on the other hand, thereby realizing the usability of the material in high-temperature fields.

[0035] (6) The optimized product density of the printed product using this process can reach more than 99.5%. After aging strengthening, the room temperature tensile strength can reach 584 MPa and the elongation can reach 15%. At a high temperature of 350°C, the tensile strength can reach 256 MPa and the elongation can reach 4.5%.

[0036] (7) After printing, the aluminum alloy of the present invention obtains a product with relatively high tensile strength and yield strength. After aging treatment, the precipitation strengthening of nanoparticles will further improve the strength of the alloy, accompanied by a partial loss of the alloy elongation. Due to the inevitable presence of defects such as pores and unfused alloys in the alloy, crack propagation is easily induced in a high temperature environment, resulting in premature failure of the material, that is, inducing high temperature brittleness of the alloy (the elongation of the alloy in service at high temperatures is reduced). BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the morphology of the SLM heat-resistant aluminum alloy powder of Example 1.

[0038] Figure 2 This is the microstructure of the SLM heat-resistant aluminum alloy of Example 1.

[0039] Figure 3 This is the microstructure of the SLM heat-resistant aluminum alloy of Example 1.

[0040] Figure 4 This is the microstructure of the SLM heat-resistant aluminum alloy of Example 4.

[0041] Figure 5 This is the microstructure of the SLM heat-resistant aluminum alloy of Example 5.

[0042] Figure 6 This is the microstructure of the SLM heat-resistant aluminum alloy of Comparative Example 2.

[0043] Figure 7 This is the microstructure of the SLM heat-resistant aluminum alloy of Comparative Example 3.

[0044] Figure 8 This is the microstructure of the SLM heat-resistant aluminum alloy of Comparative Example 4. DETAILED DESCRIPTION

[0045] The following is a specific and detailed description of the technical solutions in the embodiments of the present invention in combination with the embodiments of the present invention and the accompanying drawings. It should be noted that for ordinary technicians in this field, several modifications and improvements (including other additive manufacturing technologies, different printing parameters, etc.) can be made without departing from the principles of the present invention, and these should also be regarded as belonging to the protection scope of the present invention.

[0046] Example 1

[0047] A high-strength heat-resistant aluminum-manganese-iron alloy composition includes, by mass percentage, 4.5% manganese (Mn), 0.5% iron (Fe), 1.5% scandium (Sc), 0.75% zirconium (Zr), and the balance is Al and unavoidable impurities. The spherical pre-alloyed powder of Al-4.5Mn-0.5Fe-1.5Sc-0.75Zr is obtained by smelting the intermediate alloy ratio. The powder morphology is as follows Figure 1As shown. Before the laser powder bed fusion (L-PBF) experiment, the powder was dried in a dryer at 150°C for 4.5 hours. The median particle size of the powder was 32.8μm, and the particle size range was 10.8μm to 66.9μm, which met the particle size distribution requirements of L-PBF. The laser scanning strategy of the L-PBF experiment adopted the commonly used interlayer rotation angle of 67°. The forming parameters include: scanning power 300W, scanning speed 1100mm / s, scanning spacing 80μm, layer thickness 35μm, and substrate preheating temperature 150°C.

[0048] The aluminum matrix of the printed sample showed a heterogeneous structure with alternating distribution of coarse grains (micrometer level) and fine grains (submicrometer level). Figure 2 As shown), nano-scale strengthening phases (Al6(Mn,Fe) and Al3(Re,Zr), such as Figure 3 The brightly contrasted nanoparticles shown effectively strengthen the matrix. The alloy has a tensile strength of 306 MPa, a yield strength of 246 MPa, an elongation of 28%, and a density of 99.68%.

[0049] Then, the isothermal aging temperature was 300℃ and the holding time was 8h. The tensile strength was 501MPa and the plasticity was 8.3%; when tested at a high temperature of 350℃, the tensile strength was 179MPa and the plasticity was 4.5%.

[0050] Example 2

[0051] After the composition of the spherical pre-alloyed powder prepared by vacuum gas atomization technology in Example 1 was changed to Al-4.5Mn-0.5Fe-1.5Er-0.75Zr; the other parameters and steps were the same as those in Example 1, and an aluminum-manganese-iron-erbium-zinc alloy sample (referred to as AlMnFeErZr) was obtained. The fine grain strengthening effect and strengthening effect of Al3 (Er, Zr) were weakened, and the performance of the printed sample obtained was lower than that of Example 1. The tensile strength of the alloy was 288MPa, the yield strength was 234MPa, and the elongation was 17%; the density was 99.88%.

[0052] Then the isothermal heat aging temperature was 320℃ and the holding time was 8h. The tensile strength was 452MPa and the plasticity was 9.2%; when tested at a high temperature of 350℃, the tensile strength was 169MPa and the plasticity was 2.5%.

[0053] Example 3

[0054] After the composition of the spherical pre-alloyed powder prepared by vacuum gas atomization technology in Example 1 was changed to Al-4.5Mn-0.5Fe-0.75Sc-0.75Er-0.75Zr; the other parameters and steps were the same as those in Example 1, and an aluminum-manganese-iron-sc-h-r-e alloy sample (referred to as AlMnFeScErZr) was obtained. The fine grain strengthening effect and strengthening effect of Al3 (Sc, Er, Zr) particles induced by multi-element composite addition were enhanced, and the performance of the obtained printed sample was improved compared with Example 1. The tensile strength of the obtained printed sample was 453MPa, the yield strength was 411MPa, and the elongation was 21%; the density was 99.76%.

[0055] Then, the isothermal heat aging temperature was 300℃ and the holding time was 8h. The tensile strength was 529MPa and the plasticity was 15%; when tested at a high temperature of 350℃, the tensile strength was 197MPa and the plasticity was 3.2%.

[0056] Example 4

[0057] After the composition of the spherical pre-alloyed powder prepared by vacuum air atomization technology in Example 1 was changed to Al-6.5Mn-1.5Fe-1.5Sc-0.98Zr; before the laser powder bed fusion (L-PBF) experiment, the powder was dried in a dryer at 150°C for 4 hours. The median particle size of the powder is 45.8μm, and the particle size range is 23.4μm to 72.5μm, which meets the particle size distribution requirements of L-PBF. The laser scanning strategy of the L-PBF experiment adopted the commonly used interlayer rotation angle of 67°. The forming parameters include: scanning power 400W, scanning speed 1700mm / s, scanning spacing 140μm, layer thickness 80μm, and substrate preheating temperature 150°C. The other parameters are the same as in Example 1, and an aluminum-manganese-iron alloy sample (denoted as AlMn-1.5Fe) is obtained. Increasing the Fe content increases the volume fraction of the alloy Al6 (Mn, Fe) particles (such as Figure 4 ), the strengthening effect of the second phase particles is obvious, and the performance of the printed sample is improved compared with Example 1. The tensile strength of the printed sample is 453MPa, the yield strength is 411MPa, the elongation is 21%, and the density is 99.72%.

[0058] Then the isothermal heat aging temperature was 350℃ and the holding time was 12h. The tensile strength was 556MPa and the plasticity was 9%; when tested at high temperature of 350℃, the tensile strength was 231MPa and the plasticity was 3.8%.

[0059] Example 5

[0060] After the composition of the spherical pre-alloyed powder prepared by vacuum gas atomization technology in Example 1 was changed to Al-4.5Mn-3.5Fe-1.5Sc-0.75Zr; the other parameters were the same as in Example 1, and an aluminum-manganese-iron alloy sample (denoted as AlMn-3.5Fe) was obtained. The Fe content was further increased, and the volume fraction of the alloy Al6 (Mn, Fe) particles was further increased (such as Figure 5 ), the strengthening effect of the second phase particles is obvious, and the performance of the printed sample is improved compared with Example 1. The tensile strength of the printed sample is 487MPa, the yield strength is 423MPa, the elongation is 10%, and the density is 99.37%.

[0061] Then, the isothermal heat aging temperature was 300℃ and the holding time was 8h. The tensile strength was 584MPa and the plasticity was 5%; when tested at a high temperature of 350℃, the tensile strength was 256MPa and the plasticity was 1.5%.

[0062] Comparative Example 1

[0063] No Fe was added and other conditions were the same as in Example 1.

[0064] Through testing, the density of the sample after SLM forming is 99.2%, the tensile strength of the alloy after aging treatment is 320MPa, the yield strength is 252MPa, and the elongation is 12%. The sample is composed of a bimodal structure with alternating coarse and fine grains. The volume fraction of nano-scale fine Al6Mn is significantly reduced, which cannot effectively strengthen the alloy and affects the product performance.

[0065] Comparative Example 2

[0066] Sc and Er were not added, and other conditions were the same as in Example 1.

[0067] Through testing, the density of the sample after SLM forming is 98.5%. Lacking the heterogeneous nucleation effect of Al3(Re,Zr) particles, the grain size of the alloy is significantly increased, and it is composed of columnar crystals growing along the construction direction, such as Figure 6 As shown. After aging treatment, the tensile strength of the alloy is 275MPa, the yield strength is 240MPa, and the elongation is 8%. The sample is composed of coarse columnar crystals growing along the construction direction, and the grain refinement effect is significantly weakened; the volume fraction of nano-scale Al6Mn has not changed significantly, and the content of nano-scale coherent Al3Re precipitation phase is greatly reduced, which cannot effectively strengthen the alloy and affects the product performance.

[0068] Comparative Example 3

[0069] The printing parameters were changed to laser power of 200 W, scanning speed of 500 mm / s, scanning spacing of 50 μm, layer thickness of 120 μm, and other conditions were the same as those in Example 1.

[0070] The density of the sample formed by the above printing parameters is only 95%. Due to the low energy density, there are a lot of defects such as unfused in the sample. The tensile strength of the alloy after aging treatment is 310MPa, the yield strength is 288MPa, and the elongation is 12%. The scanning power in the scanning parameters is too low and the layer thickness is too large, resulting in too low energy density during the forming process, unable to fully metallurgically bond, resulting in defects such as unfused (such as Figure 7 ), affecting product performance.

[0071] Comparative Example 4

[0072] The aging heat treatment parameters were changed, the aging temperature was 450° C., the aging time was 12 h, and the other conditions were the same as those in Example 1. After aging, the tensile strength of the alloy was 330 MPa, and the yield strength was about 280 MPa.

[0073] Since the nano-Al6Mn particles can maintain structural stability and a slow coarsening rate in the temperature range of 250-350℃, the aging temperature reaches 450℃, and the printed bimodal structure remains stable, but the nano-scale Al6Mn particles grow abnormally (e.g. Figure 8 As shown), the performance of the alloy drops sharply.

[0074] Table 1 Summary of performance characteristics of the products obtained in the embodiments and comparative examples

[0075]

Claims

1. A high-strength and tough heat-resistant aluminum-manganese-iron alloy, characterized in that: The raw material comprises the following components by mass percentage: 4.5-9.0wt% Mn, 0.5-3.5wt% Fe, 0.2-1.5wt% Zr, 0.4-2wt% Re, and the rest is Al and inevitable impurities; the Re is Sc and / or Er.

2. The high-strength heat-resistant aluminum-manganese-iron alloy according to claim 1, characterized in that: The mass ratio of Re to Zr is 1:(0.5-0.8).

3. A high-strength heat-resistant aluminum-manganese-iron alloy according to claim 1 or 2, characterized in that: The raw materials include the following components by mass percentage: 4.5-5.0wt% of Mn, 1.5-3.5wt% of Fe, 0.2-0.75wt% of Zr, 1.5-2wt% of Re, and the rest are Al and inevitable impurities.

4. The high-strength heat-resistant aluminum-manganese-iron alloy according to claim 3, characterized in that: The aluminum matrix in the alloy is a heterogeneous structure of alternating coarse and fine grains, and primary Al6(Mn,Fe) and Al3(Re,Zr) precipitation phase particles are present on the subgrain boundaries or in the grains in the alloy matrix, and secondary Al6(Mn,Fe) and Al3(Re,Zr) strengthening phase particles with a core-shell structure exist in the matrix.

5. A method for preparing a high-strength heat-resistant aluminum-manganese-iron alloy according to any one of claims 1 to 4, characterized in that: According to the designed aluminum-manganese-iron alloy component ratio, each component is weighed, and the aluminum-manganese master alloy, aluminum-iron master alloy, aluminum-rex master alloy, aluminum-Re master alloy, and aluminum are smelted and then powdered by gas atomization to obtain aluminum-manganese-iron alloy powder; the aluminum-manganese-iron alloy powder is obtained by laser additive manufacturing and isothermal aging heat treatment.

6. The method for preparing a high-strength heat-resistant aluminum-manganese-iron alloy according to claim 5, characterized in that: The smelting temperature is 950-1100° C. After smelting, ultrasonic stirring is used to promote uniform mixing of the molten body.

7. The method for preparing a high-strength heat-resistant aluminum-manganese-iron alloy according to claim 6, characterized in that: The process parameters of the laser additive manufacturing are as follows: a laser spot diameter of 100 to 130 μm, a scanning power maintained between 300 and 400 W, a scanning speed maintained between 1100 and 1700 mm / s, a laser scanning spacing of 80 to 140 μm, a powder thickness of 35 to 80 μm, and a scanning strategy of chessboard scanning, strip scanning or honeycomb scanning; the protective gas is Ar, the oxygen content is less than 0.1%, the substrate heating temperature is 100 to 150° C., and the median particle size of the aluminum-manganese-iron alloy powder used is 20 to 48 μm.

8. The method for preparing a high-strength heat-resistant aluminum-manganese-iron alloy according to claim 5, characterized in that: The temperature of the isothermal aging treatment is 250-375° C., and the insulation time is 1-48 hours.

9. The method for preparing a high-strength heat-resistant aluminum-manganese-iron alloy according to claim 8, characterized in that: The temperature of the isothermal aging treatment is 300-350° C., and the insulation time is 8-12 hours.

Citation Information

Patent Citations

  • High-toughness aluminum alloy powder material for laser additive, preparation method and application

    CN114411023A